Repeated Ramp Tests on Stable LVAD Patients Reveal Patient-Specific Hemodynamic Fingerprint. Issue 6 (November 2018) - Imamura, Teruhiko; Burkhoff, Daniel; Rodgers, Daniel; Adatya, Sirtaz; Sarswat, Nitasha; Kim, Gene; Raikhelkar, Jayant; Ota, Takeyoshi; Song, Tae; Juricek, Colleen; Jeevanandam, Valluvan; Sayer, Gabriel; et al.
Abstract : Hemodynamic speed ramp tests are used in left ventricular assist device (LVAD) patients to guide speed adjustment and medical therapies. However, the reproducibility of these tests is unknown. In this prospective study, clinically stable LVAD patients underwent echocardiography and right heart catheterization ramp tests followed by a repeat test within 2 years as per institutional protocol. Sixteen patients (61.8 ± 10.5 years old, 50% male, eight with HeartMate II and eight with HVAD) underwent repeated ramp testing. The first test was performed 187 (42–1857) days from LVAD implant and the second test was performed 278 (126–560) days from the first test. All hemodynamic variables measured at the baseline speed remained statistically unchanged between the first and second ramp test ( p > 0.05 for all). Changes in hemodynamic parameters, as assessed by the slopes of their changes over the range of speeds tested, were also the same at the two timepoints ( p > 0.05 for all). Stable LVAD patients had similar hemodynamic profiles over the course of years including similar responses to speed changes. This suggests that ramp tests may represent a hemodynamic fingerprint; deviations from a baseline test can aid diagnosis at times of clinical deterioration or device malfunction. Abstract : Supplemental Digital Content is available in the text.